2017
DOI: 10.5301/ejo.5001063
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adjustable sutures versus nonadjustable sutures in intermittent exotropia

Abstract: Adjustable hang-back recession has no definite added advantage over nonadjustable hang-back recession in intermittent exotropia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Of the 18 studies ultimately selected for inclusion in this review, the database search revealed just two randomized controlled trials (RCT) comparing the results of AS versus NAS [7,8]. The first study included 60 children with an average age of 3.5 randomized into AS and NAS groups, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 18 studies ultimately selected for inclusion in this review, the database search revealed just two randomized controlled trials (RCT) comparing the results of AS versus NAS [7,8]. The first study included 60 children with an average age of 3.5 randomized into AS and NAS groups, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The author believes that the interpretation of the results of clinical research on the subject of AS versus NAS must go beyond just statistics. Concentrating solely on RCTs will not provide any conclusions, as so far only two such studies were performed [7,8]. Authors of recent Cochrane Database Systemic Reviews on AS versus NAS in strabismus surgery were not able to present any reliable thesis due to the scarceness of randomized studies on the subject [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies recommended adjustment within the immediate postoperative period to prevent the development of potential complications, such as healing of the conjunctiva or adherence of the muscle to the sclera. 5,[17][18][19][20] Nevertheless, Agrawal et al 21 performed adjustment 48 hours after the strabismus surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Exotropia is a common form of strabismus, with an incidence of 1% in the general population. 1 Treatment of exotropia entails either conservative measures or operative correction. When conservative measures fail to correct the condition, lateral rectus recession and/or medial rectus resection constitute the definitive treatment.…”
Section: Introductionmentioning
confidence: 99%